Effect of curry powder on the growth of listeria monocytogenes, yersinia enterocolitica and escherichia coli 0157:H7 in cook-chill beef dish - Ayub Mohd Yatim; Too , Chiou Ming; Mohd Rosni Sulaiman; Nazaruddin Ramli (Universiti Kebangsaan Malaysia, 2002)
This study was conducted to determine the effect of curry powder on the growths of Listeria monocytogenes, Yersinia enterocolitica and Escherichia coli 0157:H7 in cook-chill beef curry dish. Cook-chill beef formulas (with or without curry powder) were inoculated with approximately 6 logl0cfu/g of L. monocytogenes, Y. enterocolitica or E. coli 0157:H7 and stored at 4°C for 9 days. Population of these pathogens were monitored and viable cells was enumerated by plate count method with direct plating. Growth of Y. enterocolitica was not inhibited and reached a population approximately 8 log10cfu/g in cook-chill beef sample regardless of the absence or presence of curry powder. The population of L. monocytogenes decreased to approximately 5 log10cfu/g in the first day of storage. Even though a slight increase was observed in subsequent storage periods, the population of L. monocytogenes was still lower than the initial inoculated count. Population of L. monocytogenes was higher in cook-chill beef without curry than the beef with curry but the difference was not significant (p>0.05). Growth of E. coli 0157:H7 in both cook-chill beefs (with or without curry) were inhibited with the population showed a 3 log reduction at the end of storage time. Generally, the spices in the curry did not significantly inhibit the growth of L. monocytogenes, Y. enterocolitica and E. coli 0157:H7.